2020
DOI: 10.1111/jav.02240
|View full text |Cite
|
Sign up to set email alerts
|

Females are more determinant than males in reproductive performance in the house sparrow Passer domesticus

Abstract: Which sex has a more determinant role in reproductive performance? This is a long standing question in evolutionary ecology. Theory predicts and several pieces of evidence have indicated that females are more determinant than males. However, a direct test of this hypothesis has never been made. Here we perform such a direct test by using an alternative analytical approach, controlling for age and/or individual experience, and a captive population of the house sparrow Passer domesticus, a monogamous bi‐parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This implies that individual quality can vary over time. In fact, experimented birds tend to have a better reproductive success than first-year breeders [8,11,12], and the maturation hypothesis [13] supports the suggesting that this may be due to improvements in some skills, such as foraging ability [12], better timing of reproduction [14,15], or the increasing efficiency of the endocrine system (i.e., increase in prolactin levels) [16].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…This implies that individual quality can vary over time. In fact, experimented birds tend to have a better reproductive success than first-year breeders [8,11,12], and the maturation hypothesis [13] supports the suggesting that this may be due to improvements in some skills, such as foraging ability [12], better timing of reproduction [14,15], or the increasing efficiency of the endocrine system (i.e., increase in prolactin levels) [16].…”
Section: Introductionmentioning
confidence: 68%
“…However, too harsh conditions may decrease the heterogeneity due to the important mortality of poor-quality birds, leading to a homogenization of the phenotypes. For a given phenotype, individual performance can also fluctuate with age and/or experience [8][9][10]. This implies that individual quality can vary over time.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these results suggest that, in kittiwake pairs, reproductive outcome from the decision to lay eggs to hatching is mainly due to females. Accordingly, in several monogamous birds with biparental care including kittiwakes (Jacobsen, Erikstad, & Saether, 1995;Leclaire et al, 2010), females have been suggested to be more determinant of reproductive performance than males (Peralta-Sánchez, Colmenero, Redondo-Sánchez, Ontanilla, & Soler, 2020;Slagsvold & Lifjeld, 1990).…”
Section: Sex-specific Association Between Microbiota and Reproductive...mentioning
confidence: 99%
“…Sexes could differ in their roles and investments during the breeding season, independently of the environmental factors (Hogstad, 2005). In some species, the role of each sex is similar (Massoni et al, 2012;Wojczulanis-Jakubas et al, 2016), while in other species, sexes allocate parental care in a different manner (Paredes et al, 2006;Peralta-Sanchez et al, 2020). In passerines, it is common that females invest more energy in the current brood as they form, lay and incubate the eggs (Reid et al, 2002;Tinbergen and Williams, 2002;Goullaud et al, 2018).…”
Section: Introductionmentioning
confidence: 99%